The Economic Movement in England - Foxwell, H. S. (Quarterly Journal of Economics, 1887)
Journal Article The Economic Movement in England Get access H. S. Foxwell H. S. Foxwell Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 2, Issue 1, October 1887, Pages 84–103, https://doi.org/10.2307/1879353 Published: 01 October 1887